Mechanical Properties of Fly Ash Geopolymer Concrete Incorporating Clay Residue and Silica Fume - Pangdaeng, Saengsuree; Ngamtavee, Somporn; Tho-in, Tawatchai; Hanjitsuwan, Sakonwan; Phoo-ngernkham, Tanakorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2021)
The purpose of this paper was to investigate the mechanical properties of fly ash (FA) geopolymer concrete incorporating clay residue (CR), and silica fume (SF). The FA: CR: SF ratios were 100:0:0, 90:10:0, 90:5:5, 80:20:0, 80:15:5, 80:10:10, 70:30:0, 70:25:5, 70:20:10, and 70:15:15, respectively. Alkaline solutions of sodium silicate and 10 molar sodium hydroxide were employed as activators. The setting time, compressive strength, elasticity modulus, and Poisson's ratio of FA geopolymer concrete were studied. According to the test results, replacing CR for FA in the production of FA geopolymer concrete could result in a delay in its setting time. Compressive strength and elastic modulus of FA geopolymer concrete decreased with an increase in both CR and SF. It can be concluded that FA geopolymer concrete with 10 % CR did not negatively affect the compressive strength.